Stepwise in vitro screening of MMV pathogen box compounds against Plasmodium falciparum to identify potent antimalarial candidates - Haddijatou Mbye; Fatoumata Bojang; Fatou Kene Jaiteh; Aminata Jawara; Bekai Njie; Simon Correa; Umberto D'Alessandro; Alfred Amambua-Ngwa (International Journal for Parasitology: Drugs and Drug Resistance, 2023)
Development of resistance to deployed antimalarial drugs is inevitable and needs prompt and continuous discovery of novel candidate drugs. Therefore, the antimalarial activity of 125 compounds from the Medicine for Malaria Ventures (MMV) pathogen box was determined. Combining standard IC50 and normalised growth rate inhibition (GR50) analyses, we found 16 and 22 compounds had higher potencies than CQ respectively. Seven compounds with relatively high potencies (low GR50 and IC50) against P. falciparum 3D7 were further analysed. Three of these were tested on 10 natural P. falciparum isolates from The Gambia using our newly developed parasite survival rate assay (PSRA).According to the IC50, GR50 and PSRA analyses, compound MMV667494 was most potent and highly cytotoxic to parasites. MMV010576 was slow acting but more potent than dihydroartemisinin (DHA) 72 h after exposure. MMV634140 was potent against the laboratory-adapted 3D7 isolate, but 4 out of 10 natural Gambian isolates survived and replicated slowly despite 72 h of exposure to the compound, suggesting potential drug tolerance and risk of resistance development.These results emphasise the usefulness of in vitro testing as a starting point for drug discovery. Improved approaches to data analyses and the use of natural isolates will facilitate the prioritisation of compounds for further clinical development.